2022
DOI: 10.3390/ijms24010569
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Fuzzy Complex between RSV Nucleoprotein and Phosphoprotein to Optimize an Inhibition Assay by Fluorescence Polarization

Abstract: The interaction between Respiratory Syncytial Virus phosphoprotein P and nucleoprotein N is essential for the formation of the holo RSV polymerase that carries out replication. In vitro screening of antivirals targeting the N-P protein interaction requires a molecular interaction model, ideally consisting of a complex between N protein and a short peptide corresponding to the C-terminal tail of the P protein. However, the flexibility of C-terminal P peptides as well as their phosphorylation status play a role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
(161 reference statements)
0
1
0
Order By: Relevance
“…In one instance we observed the dissociation and rebinding of one of the simulated peptides. This is in line with the disordered character of P, but also with previous reports in RSV characterizing the interaction as giving rise to a fuzzy complex 37,42 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In one instance we observed the dissociation and rebinding of one of the simulated peptides. This is in line with the disordered character of P, but also with previous reports in RSV characterizing the interaction as giving rise to a fuzzy complex 37,42 .…”
Section: Discussionsupporting
confidence: 92%
“…P is a flexible protein with extensive intrinsically disordered regions, and the N-RNA/P interaction has been suggested to be transient, complicating structural characterization 31,32,37 . Using the deep-learning based Metapredict server 38 , we generated disorder-score plots for both HMPV N and P. In agreement with previous work, N disorder scores are globally low, while P contains significantly disordered regions (Fig.…”
Section: N Protomers Within Assemblies Are Laterally Hooked Together ...mentioning
confidence: 99%
“… 12 Nevertheless, recent investigations showed that 4,4′-dicyano-BODIPYs are significantly more resistant to trifluoroacetic acid than the corresponding difluoro-BODIPYs. 13 This enhanced chemical stability toward acid on dicyano-BODIPYs 6b , 14 was attributed to a strengthening of the B–N bonds, owing to the higher aromaticity of the former. 12b…”
mentioning
confidence: 99%